Inhibitory Effect of Vascular Endothelial Growth Factor on the Slowly Activating Delayed Rectifier Potassium Current in Guinea Pig Ventricular Myocytes. Issue 3 (26th January 2018) - Lin, Zhenhao; Xing, Wenlu; Gao, Chuanyu; Wang, Xianpei; Qi, Datun; Dai, Guoyou; Zhao, Wen; Yan, Ganxin
Abstract : Background: Vascular endothelial growth factor (VEGF) exerts a number of beneficial effects on ischemic myocardium via its angiogenic properties. However, little is known about whether VEGF has a direct effect on the electrical properties of cardiomyocytes. In the present study, we investigated the effects of different concentrations of VEGF on delayed rectifier potassium currents (IK ) in guinea pig ventricular myocytes and their effects on action potential (AP) parameters. Methods and Results: IK and AP were recorded by the whole‐cell patch clamp method in ventricular myocytes. Cells were superfused with control solution or solution containing VEGF at different concentrations for 10 minutes before recording. Some ventricular myocytes were pretreated with a phosphatidylinositol 3‐kinase inhibitor for 1 hour before the addition of VEGF. We found that VEGF inhibited the slowly activating delayed rectifier potassium current (IK s ) in a concentration‐dependent manner (18.13±1.04 versus 12.73±0.34, n=5, P =0.001; 12.73±0.34 versus 9.05±1.20, n=5, P =0.036) and prolonged AP duration (894.5±36.92 versus 746.3±33.71, n=5, P =0.021). Wortmannin, a phosphatidylinositol 3‐kinase inhibitor, eliminated these VEGF‐induced effects. VEGF had no significant effect on the rapidly activating delayed rectifier potassium current (IK r ), resting membrane potential, AP amplitude, or maximal velocity of depolarization. Conclusions: VEGF inhibited IK s in a concentration‐dependent manner through a phosphatidylinositol 3‐kinase–mediated signaling pathway, leading to AP prolongation. The results indicate a promising therapeutic potential of VEGF in prevention of ventricular tachyarrhythmias under conditions of high sympathetic activity and ischemia.